African Agricultural Transformation: perspectives from the International Institute of Tropical Agriculture - Woomer, P.L.; Lewis, S.; Mulei, W.; Adenmosum, A.; Dashiell, K.; Sanginga, N. (2025)
Agricultural transformation is a broadly recognized approach to African development and is progressing along many fronts. It pursues food and nutritional self-sufficiency, reduces reliance upon costly food imports, and advances Africa within global trade. Improved livelihood among small-scale farming households now garners increased political attention and development investments across Africa now seek to modernize smallholder agriculture in a systematic manner. Commercial seed systems based on recent genetic gains across numerous crops and countries are becoming a realizable priority. Another important target involves transitioning cassava-, maize-and rice-based systems from subsistence to commercial production strategies and adding further value to those commodities. Key drivers include substantial technical and economic empowerment of women and youth; increased advisory, value addition, marketing, and trade services through digital agriculture; and drudgery reduction through greater reliance upon scale-appropriate mechanization. The International Institute of Tropical Agriculture (IITA) and its partners are heavily involved in all areas of this transformational process, primarily through its close working relations with development banks and humanitarian donors, and through partnerships within government programs; and these efforts serve as transformation models for application across Sub-Sahara Africa